Hierarchical Structures, with Submillimeter Patterns, Micrometer Wrinkles, and Nanoscale Decorations, Suppress Biofouling and Enable Rapid Droplet Digitization. Issue 50 (23rd November 2020) - Imani, Sara M.; Maclachlan, Roderick; Chan, Yuting; Shakeri, Amid; Soleymani, Leyla; Didar, Tohid F.
Abstract: Liquid repellant surfaces have been shown to play a vital role for eliminating thrombosis on medical devices, minimizing blood contamination on common surfaces as well as preventing non‐specific adhesion. Herein, an all solution‐based, easily scalable method for producing liquid repellant flexible films, fabricated through nanoparticle deposition and heat‐induced thin film wrinkling that suppress blood adhesion, and clot formation is reported. Furthermore, superhydrophobic and hydrophilic surfaces are combined onto the same substrate using a facile streamlined process. The patterned superhydrophobic/hydrophilic surfaces show selective digitization of droplets from various solutions with a single solution dipping step, which provides a route for rapid compartmentalization of solutions into virtual wells needed for high‐throughput assays. This rapid solution digitization approach is demonstrated for detection of Interleukin 6. The developed liquid repellant surfaces are expected to find a wide range of applications in high‐throughput assays and blood contacting medical devices. Abstract : Hierarchical liquid repellant surfaces suppressing blood adhesion and clot formation, are fabricated though scalable solution‐based methods. Patterning hydrophilic regions within the liquid repellant surface provide a rapid compartmentalization of solutions into virtual wells. This can be translated into rapid, dip‐based biosensing assays with droplet digitization.